Intraarticular measurement of forces acting on the canine medial meniscus during motion - Messmer, M.; Schmökel, H.; Schawalder, P. (Veterinary and Comparative Orthopaedics and Traumatology, 2001)
Meniscal injuries are currently under much clinical investigation. With regard to tissue engineering strategies for meniscal repair or replacement, the direct measurement of forces applied on the meniscus, during range of motion, could provide important information. This in vitro study using canine cadaver limbs evaluated the possibility of measuring the tibial reaction force, at the medial meniscal level, with film pressure sensors.The sensors were placed between the medial meniscus and the tibial plateau. With different preloads of the stifle, in proportion to the dog’s total body weight measurements were taken under constant motion with intact and artificially transected cranial cruciate ligament. With an intact cranial cruciate ligament the force peak, under the cranial horn, was found in extension, and under the caudal horn in flexion. Transection of the cranial cruciate ligament led to a rise in mean force under both of the horns. The rise in mean force was higher under the caudal horn compared to the cranial horn. Transection of the cranial cruciate ligament resulted in an altered curve pattern under the caudal medial meniscal horn, which was most apparent with the highest preloads. The sensors were easy to apply, the results substantiated commonly accepted biomechanical predictions and the experimental set-up was found to be a useful tool for the investigation of forces acting on the menisci.A thin film pressure sensor was implanted under the cranial and caudal medial meniscal horn in 18 canine cadaver stifles and the forces recorded during a constant range of motion with intact and artificially transected cranial cruciate ligaments. The results reflected biomechanical predictions, and the experimental set-up was found to be a useful tool in the investigation of forces acting on the menisci.
Keywords: Dog; stifle; medial meniscus; intra-articular pressure; flim pressure sensor